Dibalik Dapur Tradisional : Analisis Permasalahan Operasional Dan Solusi Berbasis Teknologi Di Rumah Makan Ampera Ananda - Nur Fitriana; Andhika Fikri Ananda; Zalfa Hawwani Adhar; Asril Ahmad Sani; Vika Nurva Andria; Sri Andini (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
This article discusses the importance of Management Information Systems in data and information management in the MSME business of Rumah Makan Ananda in improving operational efficiency. This service aims to help MSMEs in understanding and utilizing digital technology in order to make their business more effective. The methods used are observation and interviews as well as direct assistance as training for MSMEs. The activities carried out include training on how to record finances using Warung Books, the use of QR Codes for payments, and marketing strategies that utilize technology. The results of the study show that technology-based has a positive impact and facilitates transactions that increase customer satisfaction. In conclusion, the optimal implementation of the Management Information System (SIM) can improve work efficiency and accelerate various operational processes that have a real impact on MSMEs.